(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article is aimed at studying indicators of the level of sources of formation of the real income of the population of our country. Scientific-theoretical recommendations and practical proposals have been developed to study the monetary incomes and expenses of the population of our country using the methods of economic indices, and to analyze the factors influencing the increase of the population’s well-being and real income of the population.